Technology integration-computing and analytical methods - Liu, E. (1999 IEEE Power Engineering Society Summer Meeting, 1999)
The purpose of this paper is to encourage research and development of advanced analytical algorithms to solve power system problems. Specifically, three areas are addressed: (1) utility system operation and planning; (2) energy transaction and system dispatch; and (3) power quality, reliability and energy services. The authors investigate innovations in computer applications to facilitate implementation of analytical algorithms. They advocate state-of-the-art information technology to integrate data, algorithms and applications.